Integrating Cultural Aspects in EFL Curriculum: Fostering Intercultural Awareness and Communicative Competence - Fauzi, Florence Angelaila; Syakirin Hamid, Faishal Hamdan; Suisno, Derry Pramudya; Qamariah, Zaitun (Jurnal Pendidikan Dasar dan Menengah, 2025)
This study employs a library research approach to examine the integration of cultural aspects into the English as a Foreign Language (EFL) curriculum as a means of enhancing students’ intercultural awareness and communicative competence. Academic literature on culture-based learning, teacher perceptions, and the use of authentic materials was systematically reviewed and synthesized. Findings reveal that embedding cultural dimensions into EFL instruction fosters empathy, motivation, and communication skills, yet faces persistent challenges such as limited resources, narrow textbook content, and insufficient teacher training. The study underscores the need for a culturally responsive curriculum supported by teacher capacity-building, practical strategies, and institutional support. In the context of globalization, cultural integration is not an optional supplement but a core pedagogical approach for cultivating learners who are linguistically proficient, culturally sensitive, and globally competent. Authentic materials—such as cultural stories, films, and real-life scenarios—emerge as effective tools for meaningful cultural engagement when applied through structured and reflective methods. The paper offers practical recommendations for curriculum developers, teacher educators, and policymakers to systematically embed culture into EFL education.